The Effect of Self-Resignation Exercise on the Quality of Life of HIV Patients - Evi Nurhayatun; Ratih Arianita Agung; Hanifan Danu Wijaya; Muhammad Ifham Hanif; Dhani Redhono Harioputro (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
People living with HIV/AIDS (PLWHA) are vulnerable to anxiety related to their illness, which can adversely affect inflammatory markers such as the Neutrophil-to-Lymphocyte Ratio (NLR) and overall quality of life (QOL). This study aimed to examine the effect of Self-Resignation Exercise as a complementary and holistic intervention on NLR and quality of life among HIV patients experiencing anxiety disorders. A randomized controlled trial with a pretest–posttest control group design was conducted in the Infection Subsection of Dr. Moewardi Hospital, Surakarta, starting in January 2024. Participants were HIV patients with anxiety disorders who had stable physical conditions and received routine treatment, and they were randomly assigned to a control group (n = 20) and an intervention group (n = 20). Anxiety levels were assessed using the Hamilton Rating Scale for Anxiety (HRSA), quality of life was measured with the WHOQOL-BREF, and inflammatory status was evaluated through blood tests to determine NLR. The intervention group received Self-Resignation Exercise in addition to standard care, while the control group received standard care alone. The results demonstrated a significant reduction in anxiety levels and a significant improvement in quality of life in the intervention group compared to the control group, with all measured outcomes showing p-values < 0.001. In conclusion, Self-Resignation Exercise is effective in reducing anxiety and improving quality of life in people living with HIV/AIDS, indicating its potential as a complementary approach to enhance both psychological well-being and overall health status.